Eksploitasi Marilyn Monroe dalam Film Blonde Karya Sutradara Andrew Dominik: Perspektif Psikologi Feminisme - Rosidah, Umi (Badan Pengembangan dan Pembinaan Bahasa, 2023)
This study reveals the elements of feminism in Blonde by Andrew Dominik through the perspective of feminist psychology. This study aims to 1) reveal and explore the forms of torture and exploitation experienced by Marilyn 2) find out the struggles that Marilyn Monroe did in the film Blonde to fight against this injustice. This research is a qualitative research. This study uses the technique of observing and taking notes carefully and repetitively. Data were analyzed descriptively according to the theory of feminist psychological concepts. The steps of data collection carried out by researchers are as follows. 1) watch the entire contents of the film Blonde carefully. 2) finding data in the form of one by one dialogue related to the main character's feminism in the perspective of feminism psychology contained in the film Blonde. 3) noted the significant features that show the main character's feminism in the perspective of the psychology of feminism contained in the film Blonde. 4) summarize the data related to the psychology of feminism in the Blonde film. This research resulted in an analysis and exploitation of Marilyn Monroe in the form of sexual, physical and verbal violence and no opportunity to determine her own path in life. Struggle in the form of verbal and action by Marilyn Monroe to get out of a bad work environment.AbstrakKajian studi ini mengungkapkan unsur feminisme dalam film Blonde karya Andrew Dominik melalui perspektif psikologi feminis. Penelitian ini bertujuan untuk 1) mengungkapkan dan mengeksplorasi bentuk-bentuk penindasan dan eksploitasi yang dialami Marilyn 2) mengetahui perjuangan yang dilakukan Marilyn Monroe pada film Blonde untuk melawan ketidakadilan tersebut. Penelitian ini merupakan penelitian kualitatif. Penelitian ini menggunakan teknik simak dan catat secara saksama dan repetitif. Data dianalisis secara deskriptif sesuai teori konsep psikologi feminisme. Langkah-langkah pengumpulan data yang dilakukan oleh peneliti adalah sebagai berikut. 1) menonton keseluruhan isi film Blonde secara saksama. 2) menemukan data berupa satuan dialog yang berkaitan tentang feminisme tokoh utama dalam perspektif psikologi feminisme yang terdapat dalam film Blonde. 3) mencatat ihwal-ihwal signifikan yang menunjukkan feminisme tokoh utama dalam perspektif psikologi feminisme yang terdapat dalam film Blonde. 4) meringkas data yang terkait dengan psikologi feminisme dalam film Blonde. Penelitian ini menghasilkan analisis penindasan dan ekploitasi pada Marilyn Monroe dalam bentuk kekerasan seksual, fisik, dan verbal serta tidak ada kesempatan dalam menentukan jalan hidupnya sendiri. Perjuangan dalam bentuk verbal dan tindakan yang dilakukan Marilyn Monroe untuk keluar dari situasi lingkungan kerja yang buruk.